DIVORCE HOUSEHOLD BUGIS AND AMBON PEOPLE IN AMBON - Anang Kabalmay, Husin; Tang, Mahmud; *, Nurhayatirahman; *, Tasrifintahara (IJRDO - Journal of Social Science and Humanities Research, 2016)
The purpose of this research is the high propensity of ethnic Bugis Explaining divorce in Ambon, describes the tendency of divorce for culture and local ethnic Bugis in Ambon and describe the dispute settlement mechanism of ethnic Bugis and local divorce in Ambon City. The method used in this research is basic research with ethnographic approach, or in other words, using a qualitative approach, a domain in an attempt to uncover the disputed Muslim Households (divorce) and a resolution mechanism in Ambon City. later research data. This research retrieval of data through interviews, observation and documents. Results of the study found that: (1) that the diaspora Bugis in Ambon as well as in other areas in Indonesia, basically motivated by the spirit massompe ’or wander left Reviews their homeland to other regions, etymologically, the term scope’ comes from Bugis roomates means sailing. Bugis people are very attached to the culture of migration Because agility sailing. (2) Culture divorce Bugis and Ambon is influenced by four factors important items, namely: economic factors, housekeeping habits Among ethnic, family disharmony and violence in the home (domestic violence). (3) The mechanism of settlement of Disputes between married couples domestic ethnic Bugis and Ambon consisting of three ways: (1) through local institutional mechanism for the settlement of domestic conflict that Involves family, neighborhood and community (KKSS). (2) through the mediation of figures (3) through the Formal institutions (religious court),